2013
DOI: 10.1002/jcla.21609
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence of HIV‐1 Drug Resistance in Thailand 2009–2010

Abstract: In 2010, three mutations in PR gene, M36I, H69K, and L90M, were decreased significantly. However, only one mutation in RT gene, M41L was significantly increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 89 publications
2
8
0
Order By: Relevance
“…The major TDRMs observed in this study have been reported in a previous study of HIV Drug Resistance among ART-failure individuals in Yunnan Province, which figured out mutations such as M184 V/I, K103 N, V106A, Y181C and G190A were common [ 22 ]. Notably, the similar prevalence of TDRMs has also been found among therapy-naïve HIV patients in neighboring countries Vietnam [ 20 ] and Thailand [ 27 ]. It suggested a close correlation between the TDRMs from this population and the drug resistant mutants generated during the course of ART.…”
Section: Discussionsupporting
confidence: 54%
“…The major TDRMs observed in this study have been reported in a previous study of HIV Drug Resistance among ART-failure individuals in Yunnan Province, which figured out mutations such as M184 V/I, K103 N, V106A, Y181C and G190A were common [ 22 ]. Notably, the similar prevalence of TDRMs has also been found among therapy-naïve HIV patients in neighboring countries Vietnam [ 20 ] and Thailand [ 27 ]. It suggested a close correlation between the TDRMs from this population and the drug resistant mutants generated during the course of ART.…”
Section: Discussionsupporting
confidence: 54%
“…Myanmar shares border with India, China, Bangladesh, Laos and Thailand. Similar SDRM profiles were also observed among ART-naïve HIV-1 individuals in Thailand, 42 India, 43 and China, 11,37 suggesting a possibility of cross-border transmission of HIV-1 drug resistance. This hypothesis was supported by a previous observation that TDRs circulating in the wives of IDUs in Manipur, India, were introduced from Myanmar, Vietnam and/or mainland India.…”
Section: Discussionsupporting
confidence: 67%
“… 1–3 Unfortunately, incomplete viral suppression may lead to the development of HIV drug resistance, which not only compromises therapeutic effects for an individual, but also endangers the population as a whole. 4 …”
Section: Introductionmentioning
confidence: 99%